2021
DOI: 10.1088/1757-899x/1116/1/012145
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Volume of Fluid Method in Computational Simulation of Sloshing Phenomenon

Abstract: The present study deals with the analysis of stochastic transient pressure variations and wall impacts for scaled down models of LNG carriers by using the VOF technique for interface characterization. Numerical simulation of sloshing under sway using multiphase liquid-gas condition has been carried out. Use of VOF method for multiphase numerical simulation is compared with the results of previously performed SPH study and established sloshing experiments. The efficacies of the VOF interface capturing technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The phenomenon seems to impact the majority of two-equation closing models [50,58]. Although this problem has been known for over two decades [49], the standard RANS models have been used successfully in many studies [51][52][53][54][55][56][57], and the underlying cause of this problem is not fully understood [50]. Mayer and Madsen [49] proved that k-ω and kmodels are unstable in the region of potential flow beneath the surface, where the models can suffer from exponential growth in turbulent kinetic energy.…”
Section: Assessment Of Turbulence Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon seems to impact the majority of two-equation closing models [50,58]. Although this problem has been known for over two decades [49], the standard RANS models have been used successfully in many studies [51][52][53][54][55][56][57], and the underlying cause of this problem is not fully understood [50]. Mayer and Madsen [49] proved that k-ω and kmodels are unstable in the region of potential flow beneath the surface, where the models can suffer from exponential growth in turbulent kinetic energy.…”
Section: Assessment Of Turbulence Modelsmentioning
confidence: 99%
“…Conversely, several studies have shown the importance of turbulence models in the simulation of free surface flows. Realising the lack of consensus on the importance of turbulence modelling in sloshing simulations, [51,52] assumed sloshing is a turbulent phenomenon, and standard turbulence models were used. Rhee [53] showed that a lack of turbulence modelling can lead to non-physical irregularities and instabilities in the nomodel solution.…”
Section: Introductionmentioning
confidence: 99%